2016
DOI: 10.4103/0971-4065.171233
|View full text |Cite
|
Sign up to set email alerts
|

Karyomegalic interstitial nephropathy following ifosfamide therapy

Abstract: Ifosfamide (IFO), an alkylating agent used for the management of solid organ tumors, can cause reversible Fanconi's syndrome and acute kidney injury. Karyomegalic interstitial nephropathy (KIN) is a rare form of chronic tubulointerstitial nephritis, initially described as a familial nephropathy in adults. So far, four cases of KIN have been reported in pediatric and adolescent population following treatment with IFO. We report a 22-year-old man who developed renal dysfunction following IFO therapy for relapsed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…[ 1 ] Later, the acquired cases of KIN due to toxins and viruses have been reported. [ 2 ] A case of KIN in 22-year-old male suffering from relapsed Hodgkin's lymphoma on treatment with ifosfamide was reported by Jayasurya et al [ 3 ] Another case by McCulloch et al reported three adolescent patients who recovered from their initial treatment for Ewing's sarcoma but developed a KIN attributed to ifosfamide therapy. [ 4 ] The other etiologic factors identified are heavy metals and mycotoxins, particularly ochratoxin A.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Later, the acquired cases of KIN due to toxins and viruses have been reported. [ 2 ] A case of KIN in 22-year-old male suffering from relapsed Hodgkin's lymphoma on treatment with ifosfamide was reported by Jayasurya et al [ 3 ] Another case by McCulloch et al reported three adolescent patients who recovered from their initial treatment for Ewing's sarcoma but developed a KIN attributed to ifosfamide therapy. [ 4 ] The other etiologic factors identified are heavy metals and mycotoxins, particularly ochratoxin A.…”
Section: Introductionmentioning
confidence: 99%
“…Only two biopsies (including the one with prominent fibrosis) also showed mild to moderate interstitial inflammatory infiltrate. Previous reports of ifosfamide‐induced KIN cases reported moderate to severe fibrosis with a mild to severe lymphocytic infiltrate [1,13,14]. Although KIN is classically referred to as interstitial nephritis [3], the (near) absence of inflammation in our cases suggests that the abbreviation “KIN” might be better used to refer to nephropathy, rather than nephritis.…”
Section: Discussionmentioning
confidence: 76%
“…Several studies have reported KIN in patients treated for childhood cancer as a rare event related to ifosfamide treatment, a nephrotoxic drug that is known to cause tubulopathy, reduced glomerular filtration, and renal Fanconi syndrome, but details on clinical features and pathology are lacking [1,[13][14][15][16][17][18]. Despite the small sample size, our observations suggest that tubular injury after DNA-damaging and cell stress-inducing therapy, including ifosfamide, is responsible for the clinical picture and suggest that KIN and cellular senescence should be considered as the underlying cause of early CKD in childhood cancer patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Karyomegalic changes in tubular epithelial cells result from aberrant cell division related to exposure to the toxic ifosfamide, secondarily inducing interstitial inflammation. By light microscopy, karyomegalic cells show enlarged hyperchromatic and irregular nuclei, with a high DNA ploidy [ 31 ]. Ifosfamide tubular toxicity is known but there are other factors, mainly genetic polymorphisms influencing drug metabolism that might increase the susceptibility to kidney damage.…”
Section: Drug-related Atinmentioning
confidence: 99%